Etude, évaluation et amélioration des performances du protocole de routage GPSR dans les réseaux véhiculaires Ad-hoc - Squalli Houssaini Zineb (Université Sidi Mohamed Ben Abdellah, Faculté des Sciences - Dhar El Merhaz, Fès, 2018)
:Vehicularad-hocNetwork(VANET)isadistributedandself-conﬁguring networkconsideredasasubclassofmobilead-hocnetworks(MANET)wheremobile nodes are vehicles. VANET has been suggested as an active and powerful ﬁeld for research as this type of environment encounters many challenges. Indeed, Regarding the constraints and unique characteristics of this network, routing with a very good quality of service (QoS) constitutes a major challenge. The Greedy Perimeter Stateless Routing protocol (GPSR) is one of the most promising mechanisms chosen to encounter this challenge. However, its eﬀectiveness depends entirely on geographical position information of the nodes and their precisions. Therefore, the monitoring and management of vehicle’s mobility information are very important parameters that must be taken into account. In this thesis, we propose two solutions to handle the problem of mobility and improve the eﬃciency of GPSR routing. We opt to use the vehicle’s GPS (Geographical Position System) information to predict its location in the near future. The ﬁrst solution to achieve this aim is the use of two diﬀerent deterministic prediction strategies that allow the GPSR routing protocol to make smarter routing decisions and to anticipate critical situations. Then, to attain better results, while minimizing the overhead and rout-costs, we proposed a second contribution based on a robust stochastic prediction approach using the Kalman ﬁlter algorithm. through this solution, each vehicle can update regularly and accurately the position of vehicles inside its neighborhood. Extensive simulations have been carried out to validate and to prove the eﬀectivenessoftheproposedextensionsofGPSR.Thesimulationresultsshowasigniﬁcant improvement in in the performance of our routing protocols in terms of routing cost, networkoverhead,end-to-enddelays,packetdeliveryrateandthroughputcompared to other tested routing protocols.
Keywords: Informatique; Vehicularad; hocNetworks; VANET; Geographic routing protocol; GPSR; Stochastic prediction; Kalman; Filter; QoS